La laicità importuna: laicità costituzionale e libertà religiosa (Stato, Chiese e pluralismo confessionale, 2023)
The bothersome secularity: constitutional secularity and religious freedomABSTRACT: In recent years, there has been a certain disenchantment of religious denominations with secularity. At the very time when secularity as a constitutional principle offered a broad guarantee for religious pluralism, its concrete implementation seemed to contradict this potential. The article examines how the modern, narrative conception of this principle continues to influence-and hinder-the constitutional dimension of secularity by undermining the integrative function performed by this fundamental principle.